Steel wire rod for wire drawing

A steel wire material with a controlled chemical composition and microstructure addresses vertical cracking and disconnection issues during stranding, achieving high tensile strength and stable production of wire ropes.

JP7623562B2Active Publication Date: 2025-01-29NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020061141
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-30
Publication Date
2025-01-29
Estimated Expiration
2040-03-30

AI Technical Summary

Technical Problem

Existing steel wire materials used in wire ropes face challenges in suppressing cracking and disconnection during stranding, particularly vertical cracking, which affects the stability and integrity of the wire ropes.

Method used

A steel wire material with a specific chemical composition and microstructure is developed, including C: 0.80-1.10%, Si: 0.35-2.00%, Mn: 0.30-1.20%, Al: 0.005-0.050%, P: 0.030% or less, S: 0.015% or less, N: 0.0100% or less, O: 0.0020% or less, and controlled hardness distribution, ensuring a perlite area ratio of 95% or more and initial cementite area ratio of 0.50% or less, to enhance tensile strength and stability during stranding.

Benefits of technology

The solution provides a steel wire with high tensile strength suitable for wire ropes, effectively suppressing cracking and disconnection during stranding, ensuring stable production of wire ropes with enhanced twisting characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623562000004
    Figure 0007623562000004
  • Figure 0007623562000005
    Figure 0007623562000005
  • Figure 0007623562000006
    Figure 0007623562000006
Patent Text Reader

Abstract

To provide a steel wire material for wire drawing capable of suppressing crack occurrence and disconnection during wire twisting, and more stably producing a steel wire having preferably high strength as a material for a wire rope and the like.SOLUTION: A steel wire material contains, by mass%, C:0.80-1.10%, Si:0.35-2.00%, Mn:0.30-1.20%, Al:0.005-0.050%, P:0.030% or less, S:0.015% or less, N:0.0100% or less, O:0.0020%, and the balance having Fe and impurities, having a metallographic structure, where in a cross section perpendicular to the longitudinal direction of the steel wire material, an area ratio of pearlite is 95% or more and an area ratio of pro-eutectoid cementite is 0.50% or less, and when the average value of the Vickers hardnesses in an inside area is A, the average value of the Vickers hardnesses near the surface is B, and the standard deviation is σ, then the following formulas: 360≤A≤480, 30<A-B≤70, and 0≤σ≤20 are all satisfied.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a steel wire rod for wire drawing. [Background technology]

[0002] There is a strong demand for high strength wire ropes for power transmission cables, suspension bridge cables, etc., to meet the demands for weight reduction, shortening of construction period, etc. Along with the increase in strength of wire ropes, there is also an increasing demand for high strength steel wires used as the material for wire ropes. Steel wires are generally manufactured by drawing steel wire rods. The steel wires thus obtained are optionally plated and then twisted or bundled in parallel to form a wire rope or the like made of multiple wires. One of the challenges in industrially and stably producing wire ropes that are manufactured by twisting high-strength steel wires is to prevent cracks and wire breakage during twisting. A typical crack that occurs during twisting is along the longitudinal direction of the wire, and is called delamination or longitudinal crack.

[0003] Conventional techniques for suppressing delamination (longitudinal cracking) during twisting include those described in Patent Documents 1-3, for example.

[0004] Patent Document 1 discloses a wire rod for wire drawing that is eutectoid or hypereutectoid steel, has a microstructure in which pearlite accounts for 80% or more, and has a maximum length of ferrite constituting a second phase of 10 μm or less, thereby having excellent twisting properties.

[0005] Patent Document 2 discloses a high carbon steel wire rod having excellent longitudinal crack resistance, which contains C: 0.88% to 1.10% and further contains one or both of B: 0.0050% or less and Nb: 0.020% or less, and has free N less than 0.0005%.

[0006] Patent Document 3 discloses a wire rod for steel cord that has a specified wire diameter and components, in which the C content in the surface layer is 40% or more and 95% or less of the C content in the central portion, and in which the ratio of the thickness of lamellar cementite at the center of the thickness of the surface layer to the thickness of lamellar cementite at the central portion is 95% or less, and that can prevent cracks and the like caused by the delamination phenomenon. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2002-146479 A [Patent Document 2] JP 2005-163082 A [Patent Document 3] International Publication No. 2015 / 163407 Summary of the Invention [Problem to be solved by the invention]

[0008] However, it is desirable for a steel wire material for obtaining a wire rope or the like produced by twisting a steel wire having high tensile strength to have excellent twisting processability and to more stably suppress the occurrence of cracks and breakage during twisting at an industrial level.

[0009] The present disclosure has been made in consideration of the above circumstances, and an object of the present disclosure is to provide a steel wire material for wire drawing that can more stably produce a steel wire having high strength suitable as a material for wire ropes and the like by suppressing the occurrence of cracks and breakage during wire twisting processing. [Means for solving the problem]

[0010] Means for solving the above problems include the following aspects. <1> Chemical composition, in mass%, C: 0.80-1.10%, Si: 0.35-2.00%, Mn: 0.30-1.20%, Al: 0.005 to 0.050%, P: 0.030% or less, S: 0.015% or less, N: 0.0100% or less, and O: 0.0020% or less, the balance consists of Fe and impurities, in a cross-section perpendicular to the longitudinal direction of the steel wire rod, the area ratio of pearlite is 95% or more and the area ratio of pro-eutectoid cementite is 0.50% or less, Among the cross-sections perpendicular to the longitudinal direction, when the average value of the Vickers hardness measured with a test force of 9.81 N in the region within 3r / 4 from the center when the radius is r is A, and the average value of the Vickers hardness measured with a test force of 0.98 N at a position 40 μm from the outer peripheral part toward the center is B and the standard deviation is σ, a steel wire rod for wire drawing that satisfies all of the following formulas (1) to (3). 360 ≤ A ≤ 480 ··· Formula (1) 30 < A - B ≤ 70 ··· Formula (2) 0 ≤ σ ≤ 20 ··· Formula (3) <2> The chemical composition, in mass%, replaces a part of the Fe with Cr: 0.40% or less, Cu: 0.80% or less, Ni: 0.50% or less, Mo: 0.20% or less, and V: 0.15% or less, The steel wire rod for wire drawing according to claim 1, comprising at least one or two or more selected from the group consisting of <3> The chemical composition, in mass%, replaces a part of the Fe with Ti: 0.050% or less, Nb: 0.050% or less, B: 0.0030% or less, REM: 0.030% or less, Mg: 0.030% or less, Ca: 0.030% or less, Zr: 0.020% or less, and W: 0.10% or less 3. The steel wire material for wire drawing according to claim 1, comprising one or more selected from the group consisting of: Effect of the Invention

[0011] According to the present disclosure, there is provided a steel wire material for wire drawing which can more stably produce a steel wire having high strength suitable as a material for a wire rope or the like by suppressing the occurrence of cracks and breakage during twisting. [Brief description of the drawings]

[0012] [Figure 1] 1 is a SEM image showing an example of a metal structure. [Diagram 2] FIG. 2 is a diagram for explaining the position at which Vickers hardness is measured in an internal region of a C-section of a steel wire rod. [Diagram 3] FIG. 2 is a diagram for explaining a position for measuring Vickers hardness near the surface in a C-section of a steel wire rod. [Figure 4] 1 is a diagram for explaining measurement positions of the metal structure on a C-section of a steel wire rod. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, a steel wire material for wire drawing according to one embodiment of the present disclosure (sometimes simply referred to as a "steel wire material" in the present disclosure) will be described in detail. In the following description, "%" in the chemical composition means mass %. Unless otherwise specified, a numerical range expressed with "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits. In addition, when the numerical values ​​before and after "~" are followed by "more than" or "less than," the numerical range does not include these numerical values ​​as the lower or upper limit. In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range may be replaced by the upper or lower limit of another numerical range described in stages, or may be replaced by a value shown in the examples. In addition, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.

[0014] In order to solve the above problems, the present inventors have conducted extensive research and studies into the influence of hardness distribution in steel wire material on the occurrence of cracks and wire breakage during twisting of the steel wire, and have thoroughly analyzed and examined the results, resulting in the following findings (a) to (d). (a) Most cracks originate from the surface during the stranding process of steel wires. Therefore, the properties near the surface have a large effect. By making the surface area relatively softer than the inside, the deformability near the surface is improved, and cracks and breakage during the stranding process are suppressed. (b) In order to obtain better wire stranding processability, it is necessary that the variation in hardness near the surface of the steel wire is small. (c) If the average hardness of the steel wire is too high, it becomes impossible to prevent cracks and breakage during the wire stranding process. (d) If the amount of structures other than pearlite, particularly pro-eutectoid cementite, is large, cracks and breaks are likely to occur during the wire stranding process. The present inventors have conducted further detailed experiments and research based on the findings of (a) to (d). As a result, they have found that the above-mentioned problems can be solved by adjusting, within appropriate ranges, the chemical composition, average hardness, hardness and variation in the vicinity of the surface, the difference between the average hardness and the hardness in the vicinity of the surface, and the area ratio of pearlite and the area ratio of pro-eutectoid cementite in a cross section (sometimes referred to as a "C cross section" in this disclosure) cut perpendicular to the longitudinal direction of the steel wire rod, of the steel wire rod for wire drawing, and have made the present disclosure.

[0015] The steel wire material for wire drawing according to the present disclosure is a steel wire material for wire drawing that, by undergoing wire drawing, can obtain a steel wire suitable as a material for various wire ropes, such as cables for power transmission lines and cables for suspension bridges. The tensile strength of the steel wire used as the material for the wire rope varies depending on the diameter of the steel wire, but for example, when the diameter is 1.6 to 2.0 mm, the tensile strength is preferably 2250 MPa or more, more preferably 2350 MPa or more, and even more preferably 2450 MPa or more. Also, when the diameter of the steel wire is 5.0 to 7.0 mm, the tensile strength is preferably 1850 MPa or more. Hereinafter, the description of numerical values ​​related to tensile strength will be given on the assumption that the diameter of the steel wire is 1.6 to 2.0 mm. However, the steel wire material according to the present disclosure is not limited to steel wire material for producing a steel wire having a diameter of 1.6 to 2.0 mm by wire drawing, and the diameter of the steel wire material according to the present disclosure and the diameter of the steel wire after wire drawing may be selected according to the application, etc. First, the chemical composition of the steel wire material for wire drawing according to the present disclosure will be described in detail.

[0016] <Chemical composition> C (carbon): 0.80~1.10% C is an effective component for increasing the tensile strength of steel wire rods and steel wires obtained after wire drawing. However, if the C content is less than 0.80%, the tensile strength is insufficient. For this reason, it is difficult to stably impart a high tensile strength of, for example, 2250 MPa or more to the steel wire obtained by wire drawing the steel wire rod. In addition, in order to obtain a steel wire with a tensile strength of 2350 MPa or more, it is desirable to set the C content of the steel wire rod to 0.90% or more. On the other hand, if the C content of the steel wire is too high, the steel wire becomes hard and the twisting processability decreases. If the C content of the steel wire exceeds 1.10%, it becomes industrially difficult to suppress the formation of pro-eutectoid cementite (cementite precipitated along the prior austenite grain boundaries), and the target torsion test result cannot be obtained even if other requirements are satisfied. Therefore, the C content of the steel wire is set to be within the range of 0.80 to 1.10%. In order to obtain higher tensile strength and torsion properties, the C content of the steel wire is preferably 0.85% or more and 1.05% or less, and more preferably 0.90% or more and 1.00% or less.

[0017] Si (silicon): 0.35 to 2.00% Silicon is an effective component for increasing the tensile strength of steel wire rods and steel wires obtained after wire drawing. However, if the Si content of a steel wire rod is less than 0.35%, it becomes difficult to stably impart a high tensile strength of, for example, 1850 MPa or more. On the other hand, if the Si content of the steel wire exceeds 2.00%, the target torsion test result cannot be obtained even if other requirements are satisfied. Therefore, the Si content of the steel wire is set to the range of 0.35 to 2.00%. In order to obtain higher tensile strength and torsion properties, the Si content of the steel wire is preferably 0.50% to 1.60%, more preferably 0.70% to 1.40%.

[0018] Mn (manganese): 0.30 to 1.20% Mn is an effective component for increasing the tensile strength of steel wire rods and steel wires obtained after wire drawing. Mn also fixes S in steel as MnS, preventing hot brittleness. However, if the Mn content of steel wire rods is less than 0.30%, the effect of including Mn is not sufficiently obtained. On the other hand, if the Mn content of the steel wire exceeds 1.20%, the target torsion test result cannot be obtained even if other requirements are satisfied. Therefore, the Mn content of the steel wire is set to the range of 0.30 to 1.20%. In order to obtain higher tensile strength and torsion properties, the Mn content of the steel wire is preferably set to 0.60% or more and 1.00% or less.

[0019] Al (aluminum): 0.005% to 0.050% Al is an element having a deoxidizing effect and is necessary for reducing the amount of oxygen in the steel wire rod. However, if the Al content of the steel wire rod is less than 0.005%, it is difficult to obtain the effect of including Al. On the other hand, Al is an element that easily forms hard oxide-based inclusions. If the Al content of the steel wire rod exceeds 0.050%, coarse oxide-based inclusions are significantly more likely to be formed, and wiredrawability is significantly reduced. Therefore, the Al content of the steel wire rod is set to 0.005 to 0.050%. The preferred lower limit of the Al content is 0.010%, and the more preferred lower limit is 0.020%. The preferred upper limit of the Al content is 0.040%, and the more preferred upper limit is 0.030%.

[0020] Furthermore, in the steel wire rod according to the present disclosure, in addition to the components described above, one or more of Cr, Cu, Ni, Mo, V, Ti, Nb, B, REM, Mg, Ca, Zr, and W may or may not be contained. For example, the steel wire rod according to the present disclosure may contain at least one or more elements selected from the group consisting of Cr, Cu, Ni, Mo, V, Ti, Nb, and B in order to obtain the effect of increasing the tensile strength of the steel wire. Furthermore, the steel wire rod according to the present disclosure may contain at least one or more elements selected from the group consisting of REM, Mg, Ca, Zr, and W in order to obtain the effect of improving the twisting properties of the steel wire.

[0021] Cr (chromium): 0.40% or less The inclusion of Cr is optional. Cr has the effect of increasing the tensile strength of the steel wire rod and the steel wire obtained after wire drawing. In order to stably obtain a steel wire with a tensile strength of 1950 MPa or more, it is preferable that the Cr content is 0.10% or more. However, if the Cr content of the steel wire rod exceeds 0.40%, the wire twisting processability decreases. Therefore, when Cr is intentionally contained in the steel wire rod, the Cr content is preferably within the range of 0.10 to 0.40%. The more preferable Cr content is 0.30% or less.

[0022] Cu (copper): 0.80% or less The inclusion of Cu is optional. Cu has the effect of enhancing the corrosion resistance of steel wire rods and steel wires obtained after wire drawing. In order to stably obtain this effect, a Cu content of 0.10% or more is necessary. However, if the Cu content of the steel wire rod exceeds 0.80%, the wire drawing workability decreases. Therefore, when Cu is intentionally contained in the steel wire rod, the Cu content is preferably within the range of 0.10 to 0.80%. A more preferable Cu content is 0.50% or less.

[0023] Ni (nickel): 0.50% or less The inclusion of Ni is optional. Ni has the effect of increasing the tensile strength of the steel wire rod and the steel wire obtained after wire drawing. In order to stably obtain a steel wire with a tensile strength of 1950 MPa or more, it is preferable that the Ni content is 0.10% or more. However, even if the Ni content of the steel wire rod exceeds 0.50%, the effect is saturated. Therefore, when Ni is intentionally contained in the steel wire rod, the Ni content is preferably within the range of 0.10 to 0.50%. The more preferable Ni content is 0.40% or less.

[0024] Mo (molybdenum): 0.20% or less The inclusion of Mo is optional. Mo has the effect of increasing the tensile strength of the steel wire rod and the steel wire obtained after wire drawing. In order to stably obtain a steel wire having a tensile strength of 1950 MPa or more, the Mo content is preferably 0.05% or more. However, if the Mo content of the steel wire rod exceeds 0.20%, the wire twisting processability decreases. Therefore, when Mo is intentionally contained in the steel wire rod, the Mo content is preferably within the range of 0.05 to 0.20%. The Mo content is more preferably 0.15% or less.

[0025] V (vanadium): 0.15% or less The inclusion of V is optional. V has the effect of increasing the tensile strength of the steel wire rod and the steel wire obtained after wire drawing. In order to stably obtain a steel wire having a tensile strength of 1950 MPa or more, it is preferable that the V content of the steel wire rod is 0.02% or more. However, if the V content of the steel wire rod exceeds 0.15%, the wire twisting processability decreases. Therefore, when V is intentionally contained in the steel wire rod, the V content of the steel wire rod is preferably 0.02 to 0.15%. The V content is more preferably 0.08% or less.

[0026] Ti (titanium): 0.050% or less The inclusion of Ti is optional. Ti has the effect of forming carbides or carbonitrides in the steel wire rod to improve the twisting workability. To obtain this effect, the Ti content of the steel wire rod is preferably 0.002% or more. From the viewpoint of further improving the twisting properties, the Ti content of the steel wire rod is more preferably 0.005% or more. However, if the Ti content of the steel wire rod exceeds 0.050%, coarse carbides or carbonitrides are likely to be formed, and the wiredrawing workability is reduced. Therefore, when Ti is intentionally contained in the steel wire rod, the Ti content of the steel wire rod is preferably 0.002 to 0.050%. A more preferable Ti content is 0.005 to 0.030%.

[0027] Nb (niobium): 0.050% or less The inclusion of Nb is optional. Nb has the effect of forming carbides or carbonitrides in the steel wire rod to improve the twisting workability. To obtain this effect, the Nb content of the steel wire rod is preferably 0.002% or more. From the viewpoint of further improving the twisting workability, the Nb content of the steel wire rod is more preferably 0.005% or more. However, if the Nb content of the steel wire rod exceeds 0.050%, coarse carbides or carbonitrides are likely to be formed, and the wiredrawing workability is reduced. Therefore, when Nb is intentionally contained in the steel wire rod, the Nb content of the steel wire rod is preferably 0.002 to 0.050%. The more preferable Nb content is 0.005 to 0.030% or less.

[0028] B (boron): 0.0030% or less The inclusion of B is optional. B has the effect of improving stranding workability. To obtain this effect, the B content of the steel wire is preferably 0.0003% or more. From the viewpoint of further improving stranding workability, the B content of the steel wire is more preferably 0.0007% or more. However, if the B content of the steel wire exceeds 0.0030%, coarse carbides are likely to be formed, and wiredrawing workability is reduced. Therefore, when B is intentionally contained in the steel wire, the B content of the steel wire is preferably 0.0003 to 0.0030%. A more preferable B content is 0.0007 to 0.0020%.

[0029] REM (rare earth elements): 0.030% or less The inclusion of REM is optional. If REM is included, high twisting processability can be more stably exhibited. To obtain this effect, it is preferable that the REM content of the steel wire rod is 0.002% or more. However, if the REM content of the steel wire rod exceeds 0.030%, the effect becomes saturated. Therefore, when REM is intentionally included, the REM content of the steel wire rod is preferably 0.002 to 0.030%. REM refers to a total of 17 elements, including Sc, Y, and lanthanides, and the REM content refers to the content of one type of REM when there is one type of REM, and refers to the total content when there are two or more types of REM.

[0030] Mg (Magnesium): 0.030% or less The inclusion of Mg is optional. If Mg is included, high twisting processability can be more stably exhibited. To obtain this effect, it is preferable that the Mg content of the steel wire rod is 0.002% or more. However, if the Mg content of the steel wire rod exceeds 0.030%, the effect becomes saturated. Therefore, when Mg is intentionally included in the steel wire rod, the Mg content of the steel wire rod is preferably 0.002 to 0.030%.

[0031] Ca (Calcium): 0.030% or less The inclusion of Ca is optional. If Ca is included, high twisting processability can be more stably exhibited. To obtain this effect, it is preferable that the Ca content of the steel wire rod is 0.002% or more. However, if the Ca content of the steel wire rod exceeds 0.030%, the effect becomes saturated. Therefore, when Ca is intentionally included in the steel wire rod, the Ca content of the steel wire rod is preferably 0.002 to 0.030%.

[0032] Zr (zirconium): 0.020% or less The inclusion of Zr is optional. If Zr is included, high twisting workability can be more stably exhibited. To obtain this effect, the Zr content of the steel wire rod is preferably 0.002% or more. However, if the Zr content of the steel wire rod exceeds 0.020%, coarse carbides or carbonitrides are likely to be formed, and wiredrawing workability is reduced. Therefore, when Zr is intentionally included in the steel wire rod, the Zr content of the steel wire rod is preferably 0.002 to 0.020%.

[0033] W (tungsten): 0.10% or less The inclusion of W is optional. If W is included, high twisting processability can be more stably exhibited. To obtain this effect, it is preferable that the W content of the steel wire rod is 0.02% or more. However, if the W content of the steel wire rod exceeds 0.10%, the effect becomes saturated. Therefore, when W is intentionally included in the steel wire rod, the W content of the steel wire rod is preferably 0.02 to 0.10%.

[0034] The balance other than the above elements is basically Fe and impurities. In the steel wire rod according to the present disclosure, the contents of P, S, N, and O contained as impurities are regulated as follows.

[0035] P (phosphorus): 0.030% or less P is an element that segregates at the grain boundaries of steel wire rods and reduces wiredrawability. However, if the P content of the steel wire rod is 0.030% or less, the deterioration of twistability is suppressed, and the target twist test results can be obtained while satisfying other requirements. Therefore, the P content of the steel wire rod is regulated to 0.030% or less. The upper limit of the P content is preferably 0.025%, and more preferably 0.020% or less. The lower limit of the P content is not limited, and is preferably 0% (i.e., not contained), but from the viewpoint of reducing the de-P cost, it may be more than 0% or may be 0.001% or more.

[0036] S (sulfur): 0.015% or less S is an element that reduces twisting processability. However, if the S content of the steel wire is 0.015% or less, the target twist test results can be obtained while satisfying other requirements. For this reason, the S content of the steel wire is restricted to 0.015% or less. The preferred upper limit of the S content is 0.010%. Note that the lower limit of the S content is not limited, but from the viewpoint of reducing the desulfurization cost, it may be more than 0% or may be 0.001% or more.

[0037] N (nitrogen): 0.0100% or less N is an element that reduces twisting processability. However, if the N content of the steel wire rod is 0.010% or less, the target twist test result can be obtained while satisfying other requirements. For this reason, the N content of the steel wire rod is restricted to 0.0100% or less. The preferred upper limit of the N content is 0.0070%. Note that the lower limit of the N content is not limited, but may be more than 0% or may be 0.0001% or more from the viewpoint of reducing refining costs.

[0038] O (oxygen): 0.0020% or less O is an element that easily forms oxide-based inclusions in a steel wire rod. However, if the O content of the steel wire rod is 0.0020% or less, the coarsening of the oxide-based inclusions is suppressed, and the deterioration of wiredrawability can be suppressed. Therefore, the O content of the steel wire rod is set to 0.0020% or less. A preferred upper limit of the O content is 0.0015%, and a more preferred upper limit is 0.0010%. Note that the lower limit of the O content is not limited, but may be more than 0% or may be 0.0001% or more from the viewpoint of reducing refining costs.

[0039] The balance of the steel wire rod according to the present disclosure is Fe and impurity elements. Here, the impurity elements are not elements intentionally contained during industrial production of steel, but are mixed in from raw materials such as ore and scrap, or the production environment, and are permissible within a range that does not adversely affect the effects and characteristics of the steel wire rod according to the present disclosure.

[0040] Furthermore, the steel wire material according to the present disclosure may contain other elements in addition to the above-mentioned elements and impurity elements, as long as the effects of the present disclosure are not hindered, that is, as long as a steel wire having high strength suitable as a material for a wire rope or the like can be produced more stably by suppressing the occurrence of cracks and breakage during the twisting process.

[0041] <Vickers hardness> The hardness of the steel wire rod according to the present disclosure in cross section C (cross section perpendicular to the longitudinal direction) satisfies all of the following formulas (1) to (3), where A is the average Vickers hardness measured with a test force of 9.81 N in a region within 3r / 4 from the center (hereinafter sometimes referred to as the "internal region") where r is the radius, and B is the average Vickers hardness measured with a test force of 0.98 N at a position 40 μm from the outer periphery toward the center (hereinafter sometimes referred to as the "surface vicinity") and σ is the standard deviation.

[0042] (1) 360≦A≦480 When the Vickers hardness of the internal region of the steel wire is measured under a load of 9.81 N, if the average Vickers hardness A falls below 360, it is difficult to consistently impart the tensile strength (e.g., 2250 MPa or more) required for the final product. On the other hand, if the hardness of the steel wire is too high, microcracks are likely to occur during wire drawing, and when the Vickers hardness is measured in the inner region of the steel wire under a load of 9.81 N, if the average Vickers hardness A exceeds 500, the target torsion test result cannot be obtained even if other requirements are satisfied. Therefore, the average Vickers hardness A of the inner region is set to a range of 360 to 480, and preferably 380 to 460.

[0043] (2)30 <A-B≦70 If the hardness near the surface is higher than the average hardness of the steel wire material, the stranding processability of the steel wire is reduced. Also, if the hardness near the surface is significantly lower than the average hardness of the steel wire material, the stranding processability of the steel wire is reduced. When the difference between the hardness of the inner region of the steel wire material and the hardness near the surface, i.e., "AB" is more than 30 and 70 or less, and other requirements are also satisfied, the torsion test result of the steel wire targeted in this disclosure can be obtained. Preferably, "AB" is 35 or more and 60 or less.

[0044] (3) 0≦σ≦20 When the variation in Vickers hardness increases near the surface of the steel wire, the stranding processability of the steel wire decreases. When the standard deviation σ of the Vickers hardness near the surface satisfies 0 to 20 and other requirements are also satisfied, the torsion test result of the steel wire targeted in the present disclosure can be obtained. The standard deviation σ of the Vickers hardness near the surface is preferably 0 to 15, and more preferably 0 to 12.

[0045] The Vickers hardness of the inner region and the surface vicinity of the steel wire is measured by taking samples from four locations at 500 mm intervals in the longitudinal direction of the steel wire and measuring the C-section of each sample (the cut surface at one end of each sample). The details of the measurement method will be described in the examples. For example, even if some samples (C cross sections) taken from four locations on a steel wire rod do not satisfy the relationship of formulas (1) to (3), the steel wire rod is included in the steel wire rod according to the present disclosure as long as the average value and standard deviation of the Vickers hardness calculated by measuring the four C cross sections as described above satisfy the relationship of formulas (1) to (3).

[0046] <Microstructure of steel wire rod (metal structure)> Next, the microstructure (metal structure) and characteristics of the steel wire rod according to the present disclosure will be described.

[0047] Perlite area ratio: 95% or more Area ratio of proeutectoid cementite: 0.50% or less The metal structure of the steel wire rod according to the present disclosure must satisfy an area ratio of pearlite of 95% or more and an area ratio of pro-eutectoid cementite of 0.50% or less in a cross section perpendicular to the longitudinal direction of the steel wire rod. A steel wire rod having such a metal structure has a large work hardening ability, and can be strengthened by a small amount of wire drawing, and can also obtain stable and good wire twisting workability even if the tensile strength is 2250 MPa or more. From the viewpoint of increasing the strength by wire drawing, the area ratio of pearlite of the steel wire rod according to the present disclosure is preferably 97% or more, and may be 100%. The metal structure of the steel wire rod according to the present disclosure may contain, as the remaining structure other than pearlite, one or more selected from pro-eutectoid cementite (area fraction 0.50% or less), grain boundary ferrite, bainite, and martensite, but preferably does not contain a martensite structure.

[0048] The metal structure is measured by image analysis of a photograph of the C-section of the steel wire rod taken with a field emission scanning electron microscope (FE-SEM, for example, JSM-7100F manufactured by JEOL Ltd.). Details of the measurement method will be described in the examples. Pearlite is a structure in which the ferrite phase (α) and the cementite phase (Fe3C) are alternately and continuously laminated in layers. Bainite is a structure that contains the ferrite phase (α) and the cementite phase (Fe3C) like pearlite, but since bainite is not a structure in which the ferrite phase (α) and the cementite phase (Fe3C) are alternately laminated in layers, pearlite can be distinguished from these structures by SEM photographs. Furthermore, pro-eutectoid cementite is cementite that precipitates at the grain boundaries of prior austenite, and can be distinguished from other structures by SEM photographs. Figure 1 shows an example of an FE-SEM photograph of a field of view that includes grain boundary ferrite, martensite, pro-eutectoid cementite, and bainite, which are structures other than pearlite.

[0049] <Method of manufacturing steel wire rod> Next, an example of a method for producing a steel wire rod for wire drawing according to the present disclosure will be described. Note that the method for producing a steel wire rod according to the present disclosure is not limited to the method described below.

[0050] When manufacturing the steel wire rod according to the present disclosure, the conditions in each manufacturing process are set according to the chemical composition, target performance, wire diameter, etc. so that the chemical composition and hardness conditions can be reliably satisfied. As an example of a method for producing a steel wire rod according to the present disclosure, a case will be described in which a steel containing C: 0.80-1.10%, Si: 0.35-2.00%, Mn: 0.30-1.20%, Al: 0.005%-0.050%, and the balance being Fe and impurities, containing as impurities P: 0.030% or less, S: 0.015% or less, N: 0.0100% or less, and O: 0.0020% or less is used.

[0051] As a method for casting steel, for example, in the case of continuous casting, the molten steel is melted in a converter, then subjected to sufficient electromagnetic stirring, and then reduced during solidification to obtain a cast piece.

[0052] Next, the cast slab is heated at 1250 to 1280°C for 6 to 10 hours and cooled outside the furnace to 500°C or less. Next, the cast slab is heated to 1200 to 1250°C, and then bloomed to obtain a steel slab.

[0053] The surface of the steel slab produced by the above method is ground to 0.2 to 0.5 mm, then heated to 1050 to 1100°C, and hot-rolled at a finish temperature of 900 to 950°C. The steel wire rod after finish rolling is cooled to a range of 750 to 790°C at an average cooling rate of 30°C / sec or more by a combination of water cooling and air cooling, and then immersed in a molten salt (salt bath) consisting of two tanks whose temperature can be adjusted within 5 seconds. At this time, the first tank is set to 530 to 550°C, and the second tank is set to 550 to 570°C. In this disclosure, the temperature of the steel billet in the heating furnace used for hot rolling refers to the surface temperature of the steel billet. In addition, the finish rolling temperature in this disclosure refers to the surface temperature of the steel wire rod immediately after finish rolling. The average cooling rate after finish rolling refers to the surface cooling rate of the steel wire rod after finish rolling. The surface temperatures of the steel billet and the steel wire rod can be measured by a radiation thermometer.

[0054] The steel wire material according to the present disclosure, which can be produced through the above-mentioned steps, can be drawn until the tensile strength of the steel wire is, for example, 2250 MPa or more, and then twisted, whereby longitudinal cracks and breakage can be suppressed, and wire ropes and the like can be stably produced. EXAMPLES

[0055] Next, examples of the present disclosure will be described. The conditions of the examples are one example of conditions adopted to confirm the feasibility and effect of manufacturing the steel wire rod according to the present disclosure. The steel wire rod for wire drawing according to the present disclosure is not limited to this one example of conditions. Various conditions may be adopted in the present disclosure as long as they do not deviate from the gist of the present disclosure and the object of the present disclosure is achieved.

[0056] <Steel wire rod manufacturing> Steels A1 to F2 having the chemical compositions shown in Table 1 were melted in a converter and then continuously cast. The casting conditions are also shown in Table 1. The chemical composition of each steel was measured according to the method described below. C JIS G 1211:2011 Si, Mn, P, Cr, Cu, Ni, Mo, V, Ti, Nb, Al, B, REM, Ca, Mg, Zr, W JIS G 1253:2002 S JIS G 1215:2010 N JIS G 1228:1997 O JIS G 1239:2014

[0057] [Table 3]

[0058] Next, after heating under the conditions shown in Table 1, the steel was bloomed to obtain steel billets of 122 mm square, which were then hot rolled under the conditions shown in Table 2 to produce steel wire rods.

[0059] [Table 2]

[0060] For the steel wire rods manufactured under each of the conditions in Tables 1 and 2, the average Vickers hardness, the standard deviation of Vickers hardness, the area ratio of pearlite, and the area ratio of pro-eutectoid cementite were determined by the methods described below, and are shown in Table 3. The specific measurement methods were as follows.

[0061] <Measurement of Vickers hardness in the internal region> Samples are taken from four locations at 500 mm intervals along the longitudinal direction of the steel wire, and after mirror polishing of the C-section (the cut surface at one end of each sample), the micro Vickers hardness is measured under a load of 9.81 N. Measurements are taken at 21 locations per cross section at intervals of "r / 3" (r: radius of the steel wire) as shown in Figure 2. The diamond marks (◇) in Figure 2 indicate the measurement locations. The average of the Vickers hardness values ​​measured at 84 locations (4 cross sections x 21 locations) in this way is defined as the average Vickers hardness value A. Vickers hardness measurements are made in accordance with the method described in JIS Z 2244 (2009).

[0062] <Measurement of Vickers hardness near the surface> Samples are taken from four locations at 500 mm intervals along the longitudinal direction of the steel wire rod, and the C-section (the cut surface at one end of each sample) is mirror-polished, after which the micro Vickers hardness is measured at positions 40 μm from the outer periphery toward the center, at 45° intervals in the circumferential direction, with a load of 0.98 N, as shown in Figure 3. Measurements are taken at eight locations per cross section, so the average of the Vickers hardness values ​​at a total of 32 measurement locations (4 cross sections x 8 locations) is taken as the average Vickers hardness value B near the surface. The Vickers hardness measurement method complies with the method described in JIS Z 2244 (2009).

[0063] The standard deviation σ of the Vickers hardness near the surface is calculated from the Vickers hardness at these 32 locations by a method for determining the standard deviation of a population.

[0064] <Metal structure measurement> The cross section (C section) of the steel wire cut perpendicular to the longitudinal direction is mirror-polished, and then immersed in a mixed solution of picric acid and ethanol (4 g of picric acid per 100 ml of alcohol) for 20 to 30 seconds for corrosion. Next, the structure of the corroded surface is photographed at a magnification of 5000 times using a field emission scanning electron microscope (FE-SEM: Field Emission-Scanning Electron Microscope, JEOL Ltd. JSM-7100F). Fig. 4 is a diagram for explaining measurement positions of the metal structure on the C-section of the steel wire rod. The photographing positions are one position at the center A, four positions (arbitrary positions at approximately 90° intervals on the circle C1 shown in Fig. 4) centered on a circle that is r / 2 away from the surface, where r is the radius of the steel wire rod 10, and five positions (arbitrary positions at approximately 70° intervals on the circle C2 shown in Fig. 4) centered on a circle that is r / 4 away from the surface. The area per field of view is 3.6 x 10 -4 mm 2 (18 μm long, 20 μm wide). Next, the area ratio (%) of areas other than pearlite is determined by image analysis (LUZEX manufactured by Nireco Corporation) using the photograph. The area ratio of pearlite is determined by subtracting the area ratio of areas other than pearlite from 100. The area ratio of pro-eutectoid cementite was also determined by the same image analysis. The area ratio of pearlite was calculated for each of the 10 locations, and the arithmetic average was taken as the area ratio of pearlite. The area ratio of pro-eutectoid cementite was also calculated by the arithmetic average in the same manner.

[0065] <Steel wire manufacturing> Next, a zinc phosphate coating was formed on the surface of each steel wire. After that, each steel wire coated with the zinc phosphate coating was drawn to the diameter shown in Table 3 according to a pass schedule in which the area reduction rate in each die was 16% on average, to obtain steel wires with test numbers 1 to 50.

[0066] <Measurement of tensile strength> The samples used for the tensile test of the steel wire obtained by wire drawing are three pieces of 240 mm length taken at intervals of 1 m from about 1 / 3 of the length from the end of the steel wire. The three pieces are used to perform a tensile test at a crosshead speed of 10 mm / min and a jig distance of 100 mm, and the tensile strength of each sample is measured. The average value of the tensile strengths of the three pieces is regarded as the tensile strength of the steel wire. When the steel wire had a diameter of 1.6 to 2.0 mm, the tensile strength was judged to be good if it was 2250 MPa or more, and when the steel wire had a diameter of 5.0 to 7.0 mm, the tensile strength was judged to be good if it was 1850 MPa or more.

[0067] <Torsion test> The samples used for the tensile test of the steel wire obtained by wire drawing are taken at 1 / 3 of the length from the end of the steel wire, with the length being diameter x 50 + 100 mm, every 1 m. The five samples are used to carry out a twist test five times each under the following conditions, and if no delamination occurs in any of the five samples, the twisting processability is judged to be good. Distance between chucks: Wire diameter x 50 Rotation speed: 2 rpm Axial load: Breaking load in tensile test x 0.01 Judgment method: The twisting torque-twisting angle curve is measured, and if the torque drops sharply before 1 / 2 the twisting angle at which the material breaks, it is judged that delamination has occurred.

[0068] [Table 3]

[0069] From Table 3, it is clear that in test numbers outside the conditions specified in this disclosure, at least one of the above-mentioned properties does not reach the target value. In contrast, it is clear that the test numbers which satisfy all the conditions stipulated in this disclosure have all of the above-mentioned characteristics reaching the target values.

[0070] Although the preferred embodiment and examples of the present disclosure have been described above, these embodiments and examples are merely examples within the scope of the gist of the present disclosure, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the scope of the gist of the present disclosure. In other words, the present disclosure is not limited by the above description, but is limited only by the claims, and can be modified appropriately within that scope. [Explanation of symbols]

[0071] 10 Steel wire rod A: Center of C-section of steel wire r Radius of steel wire C1: A circle at a distance of r / 2 from the surface of the steel wire at cross section C C2 A circle of r / 4 from the surface of the steel wire at the C section

Claims

1. The chemical composition, in mass%, is C: 0.80-1.10%, Si: 0.35-2.00%, Mn: 0.30-1.00%, Al: 0.008-0.040%, P: 0.025% or less, S: 0.015% or less, N: 0.0100% or less, and O: 0.0020% or less; The balance is Fe and impurities, The metal structure has an area ratio of pearlite of 95% or more and an area ratio of pro-eutectoid cementite of 0.36% or less in a cross section perpendicular to the longitudinal direction of the steel wire rod, A steel wire material for wire drawing that satisfies all of the following formulas (1) to (3), where A is an average Vickers hardness measured in a region within 3r / 4 from the center of a cross section perpendicular to the longitudinal direction with a test force of 9.81 N, where r is a radius, and B is an average Vickers hardness measured at a position 40 μm from the outer periphery toward the center with a test force of 0.98 N, and σ is a standard deviation. 360≦A≦480...Formula (1) 30<A-B≦70...Formula (2) 0≦σ≦20...Formula (3)

2. The chemical composition is, in mass %, replacing a part of the Fe, Cr: 0.40% or less, Cu: 0.80% or less, Ni: 0.50% or less, Mo: 0.20% or less, and V: 0.15% or less, The wire drawing process according to claim 1, comprising at least one or more selected from the group consisting of: Steel wire rod for use.

3. The chemical composition is, in mass %, replacing a part of the Fe, Ti: 0.050% or less, Nb: 0.050% or less, B: 0.0030% or less, REM: 0.030% or less, Mg: 0.030% or less, Ca: 0.030% or less, Zr: 0.020% or less, and W: 0.10% or less The steel wire material for wire drawing according to claim 1 or 2, comprising one or more selected from the group consisting of:

Citation Information

Patent Citations

  • High-strength steel wire rod excellent in wiredrawability

    JP1987256950A

  • Wire rod for wire drawing having excellent twisting characteristic and its production method

    JP2002146479A

  • High carbon steel wire rod having excellent longitudinal crack resistance

    JP2005163082A

  • Wire material for high strength steel cord

    WO2015163407A1

  • Wire rod

    WO2018117157A1